The effect of pressure tuning on the structure and mechanical properties of high-entropy carbides. (15th July 2022) - Guan, Shixue; Lin, Weitong; Liang, Hao; Liang, Wenjia; Tian, Yi; He, Duanwei; Peng, Fang
Abstract: High-purity (Ta0.2 Nb0.2 Hf0.2 Zr0.2 Ti0.2 )C high-entropy ceramics are successfully synthesized using high-pressure solid-phase reactions. The high-entropy phase formation route and the effect of pressure tuning on the structural and mechanical properties of the ceramics are systematically investigated. An interesting process is observed whereby a double phase high-entropy carbide is formed, followed by the defusing of one phase into another, and the eventual formation of a high-entropy phase. Moreover, an abnormal, pressure-induced enhancement of the bulk modulus and strength is observed, resulting from the crystal plane distortion in high-entropy carbides. These results reflect the unusual lattice distortion effects of continuous, pressure-induced tuning on the structure and properties of high-entropy carbides. Graphical abstract: Image, graphical abstract